Avoiding nightmares in teaching digital methods - Nunn, Christopher Alexander (Interdisciplinary forum of digital textual sciences, 2018)
„One can’t go wrong with this,“ I thought. Well - now I know better! In an academic exercise, I presented some digital methods to teacher trainees. I wanted to enable them to use these methods deli…